Metal Ion-Induced Structural Changes Of Bovine Blood Coagulation Factor X1 - Freyssinet, J M (Thrombosis and Haemostasis, 1981)
Wheat germ lectin (W.G.A.) has been used as a macromolecular probe to investigate metal ion-induced conformational changes of bovine Factor X1 . The classical precipitin reaction between lectin and glycoprotein only occurs when certain metal ions are present. Precipitin reactions were followed by recording turbidity at 330 nm.It has been verified that W.G.A. lectin activity is insensitive to the presence of either EDTA, Ca(II), Mn(II) or Mg(II). Ca(II) and Mn(II) are able to induce a precipitin reaction between W.G.A. and Factor X1. The reaction is slow at metal ion concentration of 2.5 mM but becomes more rapid when higher divalent cation concentrations are used. Ca(II) and Mn(II) have comparable efficiency, Mg(II) is totally ineffective in promoting such a precipitin reaction. Halftimes of precipitin reactions range from 7 minutes at 2 mM Ca(II) to 0.3 minutes at 100 mM Ca(II). Above 100 mM Ca(II) or Mn(II), increasing metal ion concentration would slow down the reaction ; increasing the ionic strength had a similar effect. Although very slow and weak, the precipitin reaction could still occur at high ionic strength up to 0.8 M. The various conditions that give rise to a precipitin reaction demonstrate that Factor X1 must undergo a cation- catalyzed transit ion which allows binding of lectin to its specific sugar(s). This leads to suggestions on the nature of this structural change. When compared to metal-ion induced protein transition involved in protein-phospholipid binding described in the literature, the difference of divalent cation specificity and active concentration in both of these studies point out that the conformational changes have to be different.